AN OVERVIEW ON MECHANISM OF GENE EXPRESSION REGULATION - Elsahookie, M. M.; Cheyed, S. H.; Dawood, A. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
Transcription factors, enhancers, promoters, and translation of genetic code is still in a wide argument of different views in many living organisms for their poorly characterized at the molecular level. It was shown that the coexistence of high mono – methylation levels of lysine 4 of histone H3 is considered a signature of enhancers. Gene expression could be altered by epigenetic and some biotic and abiotic stresses. Some sugars, hormones or amino acids could also alter gene expression. However, some investigators have shown that increased methylation  at promoters was associated with down – regulated protein – coding gene expression . In genomic DNA methylation levels, it was found 24 nt small RNAs only were correlated with methylation. Other investigators have set framework for modelling gene regulation, three dimensions were set to draw the graph framework; DNA microstates (vertices), the transitions between microstates, (edges) and the transition rates (edge labels). They believed that their graph will provide a broader foundation for understanding how genes regulate their expressions. More recently, a team of Australian investigators in Medical Res. have shown a new i-motifs; a four–stranded DNA knot in living human cells. These i- motifs were believed to be responsible in helping genes to switch on or off. Future investigations in gene expression will probably be shown in different models than we have learned.